MENERAPKAN MODEL “PROBLEM BASED LEARNING” PADA MATERI “GAYA DI SEKITAR KITA” DI KELAS IV SD NEGERI 1 DUKUHWALUH BANYUMAS - Intan Ayu Nur Rizki; Wakhudin (EDU RESEARCH, 2025)
This study aims to analyze the implementation of Problem Based Learning (PBL) in learning the material "Forces Around Us" in grade IV of SD Negeri 1 Dukuhwaluh Banyumas. This study uses a qualitative-descriptive approach with a case study method. Data were obtained through observation, interviews, and documentation studies. The results of the study indicate that the implementation of PBL increases student participation, conceptual understanding, and critical thinking and problem-solving skills. Students are more active in group discussions, conducting experiments on thrust forces, and drawing conclusions based on observation results. However, several obstacles found include teacher readiness in compiling teaching modules, differences in student understanding levels, and limited facilities and infrastructure. These obstacles can be overcome through teacher training, peer tutoring, and the provision of teaching aids. Thus, PBL has proven to be an effective learning method in increasing student engagement and learning outcomes. The recommendation of this study is to increase school support in providing learning media and developing teacher competencies in implementing PBL